Pengaruh Kompensasi Terhadap Kepuasan Kerja Pada Dealer Honda Kota Sorong - Elsa Remetwa; Susana Magdalena Welly Muskita (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study contains the effect of compensation on job satisfaction in Honda dealers in Sorong City, The research method used in this study is quantitative. The data used was primary data sourced from the distribution of questionnaires to employees of Honda dealers in Sorong City totaling 35 respondents. The data processing process is carried out using the help of SPSS version 29. Based on validity test, reliability test, simple linear regression analysis and hypothesis testing using t test, F test and determinant test. These results show that the Compensation variable (X) has a significant influence on Job satisfaction (Y), because the significance value is less than 0.05, which is 0.000. The adjusted R2 (adjusted R square) determination coefficient has a value of 0.577 which means that the compensation variable (X) has an effect on job satisfaction (Y) by 57.7%, while the remaining 0.423 or 42.3% (100% - 57.7%) is influenced by the variables that are not studied in this study.